2020
DOI: 10.1148/radiol.2020192509
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of LIBRA Software for Fully Automated Mammographic Density Assessment in Breast Cancer Risk Prediction

Abstract: BREAST IMAGING I ncreased mammographic density has been shown consistently to be an independent risk factor for breast cancer (1-3) and a factor associated with decreased mammographic sensitivity because of masking of tumors within dense breast tissue (4-7). Several approaches have been developed to assess breast density in full-field digital mammography (FFDM) (8-13). The most commonly used method in the clinical setting is the visual grading of breast density by the interpreting radiologist into one of four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 28 publications
1
28
1
Order By: Relevance
“…The importance of volumetric density estimates in further refining breast cancer risk assessment has been shown in previous studies (10,20), where breast cancer associations were highest for Volpara VPD% compared with semi-and fully automated APD% measures. However, both studies evaluated modelapproximated VPD% derived from raw DM, not from DBT volumes, as we did here.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The importance of volumetric density estimates in further refining breast cancer risk assessment has been shown in previous studies (10,20), where breast cancer associations were highest for Volpara VPD% compared with semi-and fully automated APD% measures. However, both studies evaluated modelapproximated VPD% derived from raw DM, not from DBT volumes, as we did here.…”
Section: Discussionmentioning
confidence: 82%
“…Area-based density evaluation from DM.-The publicly available LIBRA software (version 1.0.4) (7), previously used in various research studies of breast density (20)(21)(22)(23), can calculate area-based density from either raw or processed DM images (8). Briefly, LIBRA partitions the breast region into density clusters of similar gray-level intensity, which are then aggregated into the final dense tissue segmentation.…”
Section: Breast Density Evaluation From Dbt and Dmmentioning
confidence: 99%
“…It analyzes full-eld digital mammography images based on gray-level values and segments them into dense and non-dense areas [31]. LIBRA has been validated by Gastouni et al [32], among others. Studies have revealed an association between dense LIBRA area and breast cancer [32].…”
Section: Mammographic Images and Image Analysis Systemsmentioning
confidence: 99%
“…The lack of a standardized and easily implemented MD assessment continues to be a major impediment to widespread application of MD in clinical settings, but is the subject of robust research and technological development. Recent development of fully-automated methods to produce continuous and reliable MD measurement, and notable efforts to elucidate risk-relevant mammographic information that go beyond conventional MD measures (e.g., degree of brightness or spatial distribution of mammographic features), promise to offer more readily feasible and meaningful integration of MD in clinical risk stratification (8)(9)(10).…”
Section: MDmentioning
confidence: 99%